2000
DOI: 10.1002/1097-0223(200009)20:9<709::aid-pd910>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Trends in live birth prevalence of Down syndrome in the Northern Netherlands 1987-96: the impact of screening and prenatal diagnosis

Abstract: In the Northern Netherlands, we examined the live birth prevalence of Down syndrome (DS) and the impact of maternal serum screening (MSS) and prenatal cytogenetic diagnosis (PCD) during the period 1987–96. In this period the live birth prevalence, based on the maternal age distribution and the age specific risk of delivering a child with DS was expected to increase from 1.26 in 1987 to 1.62 in 1996. The introduction of MSS in 1991 made PCD available to women of all ages. Nevertheless, the utilization of PCD re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, the worldwide birth incidence of DS has actually decreased from what it could have been by 2–18% per year (table 2). 21 22 23 24 25 26 27 28 29 30 31 32 33 34 For example, in the USA, there would have been a 34% increase in the number of babies born with DS between 1989 and 2005, in the absence of prenatal testing 32 35. Instead, there were 15% fewer babies born, representing a 49% decrease between the expected and observed rates.…”
Section: What Has Been the Impact Of Prenatal Testing On The Birth Inmentioning
confidence: 99%
“…However, the worldwide birth incidence of DS has actually decreased from what it could have been by 2–18% per year (table 2). 21 22 23 24 25 26 27 28 29 30 31 32 33 34 For example, in the USA, there would have been a 34% increase in the number of babies born with DS between 1989 and 2005, in the absence of prenatal testing 32 35. Instead, there were 15% fewer babies born, representing a 49% decrease between the expected and observed rates.…”
Section: What Has Been the Impact Of Prenatal Testing On The Birth Inmentioning
confidence: 99%
“…Prenatal screening tests for Down syndrome (DS) have been shown to give reliable and reproducible results, with high sensitivities and low false positive rates (FPR) (Wald et al, 2003). Significant reductions in the birth prevalence of DS and the number of prenatal diagnostic tests performed have been documented following the introduction of some prenatal screening programmes (Cheffins et al, 2000;Wortelboer et al, 2000;Khoshnood et al, 2004;Jou et al, 2005;Ekelund et al, 2008). However, despite the high sensitivity and increasing uptake of screening tests in Victoria, Australia, since its introduction in 1996 (Jaques et al, 2006(Jaques et al, , 2007, the overall birth prevalence of DS has remained relatively constant, particularly in older women (Collins et al, 2008), and similar trends have also been seen elsewhere (Brajenovic-Milic et al, 2008;Morris and Alberman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of DS among births in a population is influenced by the proportion of pregnancies among women 35 years of age and older and by the availability and use of prenatal diagnosis. However, despite the wide availability of prenatal diagnosis and the option for elective termination of affected pregnancies, several studies have reported little or no change in the prevalence of DS among livebirths (Carothers et al, 1999; Hoshi et al, 1999; Cheffins et al, 2000; Rosch et al, 2000; Wortelboer et al, 2000; Binkert et al, 2002; Iliyasu et al, 2002; Bell et al, 2003; Khoshnood et al, 2004; Dolk et al, 2005; Crane and Morris, 2006). In fact, in some populations, a recent increase in the prevalence of DS among livebirths has been noted.…”
Section: Introductionmentioning
confidence: 99%